SOCIO-POLITICAL DYNAMICS TAKING PLACE AT KUTA TRADITIONAL VILLAGE, BALI: FROM DESA ADAT (TRADITIONAL VILLAGE) TO DESA PEKRAMAN (ANOTHER TYPE OF TRADITIONAL VILLAGE) IN THE PERSPECTIVE OF CULTURAL STUDIES - Wesna Astara, I Wayan; Parimartha, I Gde; Sirtha, I Nyoman; Mariyah, Emiliana (E-Journal of Cultural Studies; Vol. 4, No. 2 Juli 2010)
This research explores the socio-political dynamics taking place at KutaTraditional Village, Bali: from desa adat (traditional village) to desa pekraman (anothertype of traditional village) in the perspective of cultural studies. There are three problemsformulated in this research. The first problem is how the socio-political dynamics fromdesa adat (traditional village) to desa pekraman (another type of traditional village) tookplace at Kuta? The next problem is how the traditional village interacted with theadministrative village at Kuta? And the last problem, which is the third, is what were theimpacts and meanings of the change from desa adat to desa pekraman? In this studyqualitative method was employed. And the data needed was obtained by employing thetechnique of in-depth interview, the technique of participatory observation, anddocumentation study. To give responses to the problems mentioned above, the theory ofhegemony, the theory of deconstruction, the theory of conflict, the theory of power andknowledge and the theory of eclectically symbolic interaction were applied.The findings show that the socio-political dynamics taking place Kuta TraditionalVillage resulted in turbulence among the villagers. This is indicated by the Local Rulesand Regulations (Perda) issued by Desa Pekraman of Number 3 of Year 2001. Thiscould be responsible for the factors of pro’s and con’s in various aspects. Clause (6) ofArticle 3 of the Perda of Number 3 of Year 2001 was reversed by the leaders of KutaTraditional Village. They did not agree that non-Hindu people were included as thetraditional village members.As far as the interaction between the traditional village and the administrativevillage is concerned, the governmental hegemony took place. The government appliedhegemony to the traditional village through the administrative village in the form of rulesand regulations. The local rules and regulations issued by the desa pekraman, as a legalproduct in Bali, are left crystallized sociologically, philosophically, and juridically. However, the dynamism of the traditional villagers in Bali will “justify” to what extentsuch rules and regulations are justified and to what extent they are protective. The changeof the Perda issued by the desa adat into that issued by the desa pekraman was notfollowed by Kuta Traditional Village by replacing the awig-awig (rules and regulations)issued by the desa adat or making loose agreements to adapt to the higher rules andregulations in addition to anticipating the migrants through the change in rules andregulations applicable at Kuta Traditional Village. Basically, the socio-political dynamicstaking place at Kuta Traditional Village as a consequence of the change made from desaadat to desa pekraman resulted in no important things. However, from the “substance”point of view, the change can be seen in the formation of Majelis Desa Pekraman (theAssembly of Desa Pekraman) (Article 14), which is formed from below, and in theappearance of pecalang (traditional security) which is responsible for the security andorderliness of the village area especially when traditional and religious activities areperformed. Actually, pecalang is an “old product” which is newly packaged with “newenthusiasm” and is included in the Perda of Number 3 of Year 2001 issued by the DesaPekraman . The meanings created by the change made from Desa Adat to DesaPekraman are transformational, dialogic and dynamic. The desa pekraman is in the ongoingprocess (which will never come to an end) of being integrated into theadministrative village.The findings show that there were multiple interpretations given by the leaders ofKuta Traditional Village, as far as the articles in the Perda issued by the Desa Pekramanare concerned, governmental hegemony which was in the form of Rules and Regulationsas the social transformation of the State by which villages are organized.
Keywords: socio-political dynamics, traditional village, administrative village, and awig-awig (locally -made rules and regulations) of the desa adat.